センジョウ カンソク データ ニ モトヅク ナンキョク リュツォ・ホルムワン テイチャクヒョウ ノ カキ ニオケル ヒョウアツ オヨビ セキセツシン ブンプ トクセイ ニツイテ - 宇都, 正太郎; ウト, ショウタロウ; 下田, 春人; シモダ, ハルヒト; 泉山, 耕; イズミヤマ, コウ; 牛尾, 収輝; ウシオ, シュウキ; 青木, 茂; アオキ, シゲル; 橋田, 元; ハシダ, ゲン; et al. (2004)
P(論文) 南極観測船「しらせ」船上で取得された海氷観測結果をもとに,リュツォ・ホルム湾定着氷の夏季における氷厚及び積雪深分布について考察した.ビデオ観測結果から求めた各年の全氷厚(氷厚+積雪深)確率密度分布は薄氷型と厚氷型に分けられることがわかった.また大陸沿岸から約km圏内では全氷厚及び積雪深は沿岸に向かって漸減する傾向を示した.これは北東方向の卓越風による積雪輸送によると考えられる.電磁誘導法によって観測された全氷厚分布には不連続的な変化が認められた.NOAAAVHRR画像と比較した結果,不連続の位置は定着氷流出後の再結氷域における一年氷と,未流出の厚い多年氷との境界に一致することがわかった.定着氷の流出範囲は年によって大きく変動する.流出位置が沖側に後退すると厚い多年氷域の割合が多くなり厚氷型になり,沿岸に近づくと積雪影響も相まって厚い多年氷域が縮小または消滅し,薄氷型になるというメカニズムが明らかになった. Sea ice observations have been conducted onboard the Antarctic Research Vessel Shirase" since . The authors summarize these data to investigate spatial and inter-annual variability of sea ice thickness and snow depth of the summer land-fast ice in Lutzow-Holmbukta. Probability density functions of annual total thickness (ice thickness+snow depth) derived from video observations are categorized into two types, i.e. a thin-ice and a thick-ice type. The total thickness distributions observed by the electro-magnetic inductive method have a clear discontinuity, which reects the past break-up of the land-fast ice. Thin rst-year ice develops oshore of this location, while multi-year ice mostly develops onshore. Ice thickness and snow depth gradually decrease toward the coast within about km oshore, probably due to snow drift driven by the strong northeasterly wind. It is concluded that the past breakup of the land-fast ice as well as snow depth have dominant inuence on the spatial distribution of ice thickness in Lutzow-Holmbukta. The extent of break-up varies signicantly year by year. The smaller extent enhances the development of thick multi-year ice, while the larger extent, coupled with the inuence of snow drift, enhances reduction or extinction of thick multi-year ice. departmental bulletin paper